Voluntary corporate disclosures and tangible brand elements in financial advertisements for consumer buy-in: a study on Malaysian unit trusts - Thanaseelen Rajasakran,; Thinavan Periyayya,; Santhidran Sinnappan,; Sharon Wilson, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to explore the appeal of voluntary corporate disclosures in advertisements for unit trust schemes (UTS). Purposive sampling was used to recruit 25 Malaysian working adults aged between 20 to 70 years old as respondents. In-depth interviews were conducted via Zoom for an average duration of 60 to 90 minutes. Interviews were audio recorded and transcribed for thematic analysis. Findings showed that tangible brand components, namely logo, color schemes, typeface, and names which appear in financial advertisements, create brand awareness through key themes such as easy recognition, credibility, association, confidence, and familiarity. Financial advertisements in the media are important to create brand recognition, recall and familiarity. Brand awareness and attitude are vital in advertising financial products for eventual buy-in, especially among consumers. Brands should be recognized, remembered, and viewed positively in any type of unit trust advertising. The major deciding factor for brand awareness, attitude and purchasing decision is corporate voluntary disclosure. Financial products are pre-conceived as risky and require careful examination of trustworthy corporate tangible brand elements contained in an advertisement. Negative internal motivation among potential investors requires more reliable corporate information, including celebrity endorsements and fees charges. In fact, positive motivation for trust can be enhanced when celebrities and testimonials are involved, whereas fees charged is not crucial. This study intends to provide policy makers insights into persuading consumers to buy-in and invest in unit trust via appropriate corporate advertising strategies to target audience for effective advertising.